Transformation of HF in Regions of Russia: Retrospective Experience and Modern Dynamics - KAZAKOVA, Lyudmila; KAZAKOV, Mikhail; KOROBEINIKOVA, Larisa; SHIKHALIEVA, Dzhannet; DUBSKAYA, Oksana (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The problems of development of small-scale sector of agrarian economy in Russia require an adequate scientific support. Economic and social viability of managing of household farms (HF) by population is significantly influenced by a number of factors and conditions of various etiology and localization level. This paper aims to analyze the system and historical peculiarities during formation of modern institutional, paradigmatic and socio-economic status of HF in the context of their ring fencing in a special group of state agricultural policy. The conceptual approaches and practical recommendations for determination of the promising directions of stimulating the development of small-scale agribusiness sector are presented in the research; ‘roadmapping’ of this process during various periods of planning and forecast have been made. According to the results of analytical procedures a forecast of the main parameters of HF production activity has been performed. The results of the study have shown that, taking into account apparent archaic and rudimental character of HF as economic units, their development prospects in challenging market and crisis conditions are in reconsideration of the paradigm of state policy towards them. The authors have made a heuristic attempt, taking into consideration systematic and genetic peculiarities of functioning of the entity under consideration, to form a strategic futurology vision of further harmonious ‘embedding’ of HF of the population into the modern ‘picture’ of agro-social environment.